Alternative Monetary Policy Rules for India - Kapur, Muneesh; Patra, Michael (Washington, D.C. : International Monetary Fund, 2012)
This paper empirically evaluates the operational performance of the McCallum rule, the Taylor rule and hybrid rules in India over the period 1996-2011 using quarterly data, with a view to analytically informing the conduct of monetary policy. The results show that forward-looking formulations of both rules and their hybrid version - setting a nominal output growth objective for monetary policy with an interest rate instrument - outperform contemporaneous and backward-looking specifications, especially when targeting core components of GDP and inflation, and combine the best parts of efficiency and discretion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet